Tranexamic acid: a narrative review of its current role in perioperative medicine and acute medical bleeding - Bouras, Marwan; Bourdiol, Alexandre; Rooze, Paul; Hourmant, Yannick; Caillard, Anaïs; Roquilly, Antoine (Frontiers in Medicine, 2024)
Purpose: Tranexamic acid (TXA) is the most widely prescribed antifibrinolytic for active bleeding or to prevent surgical bleeding. Despite numerous large multi-center randomized trials involving thousands of patients being conducted, TXA remains underutilized in indications where it has demonstrated efficacy and a lack of harmful effects. This narrative review aims to provide basic concepts about fibrinolysis and TXA's mode of action and is focused on the most recent and important trials evaluating this drug in different hemorrhagic situations.Methods: We selected every low bias RCT, and we highlighted their strengths and limitations throughout this review.Principal Findings: While TXA appears to have a favorable benefit-risk ratio in most situations (trauma, obstetrics, at-risk for bleeding surgeries) evidence of benefit is lacking in certain medical settings (SAH, digestive bleeding).Conclusion: Although in some situations the drug's effect on significant outcomes is modest, its favorable safety profile allows it to be recommended for trauma patients, in obstetrics, and in scheduled surgeries at risk of bleeding. However, it cannot be recommended in cases of spontaneous intracranial bleeding, subarachnoid hemorrhage (SAH), or gastrointestinal bleeding.